2017
DOI: 10.1146/annurev-genet-120116-024554
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration Genetics

Abstract: Understanding how and why animals regenerate complex tissues has potential to transform regenerative medicine. Here we present an overview of genetic approaches that have recently been applied to dissect mechanisms of regeneration. We describe new advances that relate to central objectives of regeneration biolsts researching different tissues and species. These objectives include defining the cellular sources and key cell behaviors in regenerating tissue; elucidating molecular triggers and brakes for regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 138 publications
(168 reference statements)
1
33
0
Order By: Relevance
“…Approximately 40 embryos were used for each of the regeneration analyses and then genotyped to study the genotype-phenotype correlation. smn1, gemin3, and gemin5 mutations affect the regeneration of multiple tissues Regeneration of different tissues can be achieved by utilizing a common set of molecular pathways and many genes are pan-regenerative in that they are induced and essential regardless of the specific injured tissue 21 . Both smn1 and gemin5 genes were involved in regulating the regeneration of multiple tissues including neuromasts, caudal fins, and livers 14 .…”
Section: Regenerative-deficient Mutants Show Reduced Proliferation Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 40 embryos were used for each of the regeneration analyses and then genotyped to study the genotype-phenotype correlation. smn1, gemin3, and gemin5 mutations affect the regeneration of multiple tissues Regeneration of different tissues can be achieved by utilizing a common set of molecular pathways and many genes are pan-regenerative in that they are induced and essential regardless of the specific injured tissue 21 . Both smn1 and gemin5 genes were involved in regulating the regeneration of multiple tissues including neuromasts, caudal fins, and livers 14 .…”
Section: Regenerative-deficient Mutants Show Reduced Proliferation Afmentioning
confidence: 99%
“…Hair cell regeneration studies in zebrafish have uncovered numerous genetic factors and molecular pathways that are associated with the regeneration of hair cells 18 ; conversely, random mutagenesis studies revealed that mutations in only a small number of genes actually alter hair cell regeneration specifically 14,17,19,20 . There is consistently a gap between the number of genes transcriptionally associated with regeneration and the number of genes essential for regeneration in other tissues as well 21,22 . Therefore, seeking novel genes essential for tissue regeneration is pivotal in understanding the core molecular mechanisms of wound healing, and for ultimately advancing regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Regeneration of different tissues can be achieved by utilizing a common set of molecular pathways and many genes are pan-regenerative in that they are induced and essential regardless of the specific injured tissue (17). Both smn1 and gemin5 genes were involved in regulating the regeneration of multiple tissues including neuromasts, caudal fins, and livers (10).…”
Section: Smn1 Gemin3 and Gemin5 Mutations Affect The Regeneration Omentioning
confidence: 99%
“…Hair cell regeneration studies in zebrafish have uncovered numerous genetic factors and molecular pathways that are associated with the regeneration of hair cells (14); conversely, random mutagenesis studies revealed that mutations in only a small number of genes actually significantly alter hair cell regeneration specifically (10,13,15,16). There is consistently a gap between the number of genes transcriptionally associated with regeneration and the number of genes essential for regeneration in other tissues as well (17,18). Therefore, seeking novel genes essential for tissue regeneration is pivotal in understanding the core molecular mechanisms of wound healing, and for ultimately advancing regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Technological and interdisciplinary approaches have morphed regeneration science into a formidable collaborative effort aimed at understanding how cell-based strategies can be used to restore damaged or diseased tissues and organs (Stocum, 2001). The idea for a Special Issue on regeneration was conceived following a satellite symposium held at the 75th Annual Meeting of the Society for Developmental Biology in Boston, MA, titled: “Evolution of regenerative abilities: recapitulation of development or novel mechanisms?” The symposium brought together prominent senior scientists and new investigators in the field of regenerative biology, who highlighted how broad application of new transgenic technologies and the accessibility of comparative genomics are opening frontiers in stem cell and regenerative biology research using classic and emerging models (Chen and Poss, 2017; Sánchez Alvarado and Tsonis, 2006). Much of the discussion centered on how the study of regeneration, at its core, shares fundamental similarities with the goal of understanding the basic principles underlying organismal development (e.g., cell differentiation, morphogenesis, and tissue patterning) (Brockes and Kumar, 2008; King and Newmark, 2012; Tanaka and Reddien, 2011).…”
mentioning
confidence: 99%